2022
DOI: 10.3325/cmj.2022.63.343
|View full text |Cite
|
Sign up to set email alerts
|

The burden of viral lower respiratory tract infections during the neonatal period: six-year experience at a tertiary referral hospital

Abstract: AimTo identify the epidemiological and clinical features of acute viral lower respiratory tract infections (LRTI) caused by respiratory syncytial virus and other respiratory viruses, and to determine the risk factors for the severe disease among neonates. MethodsWe retrospectively reviewed the records of neonates aged up to 44 postconceptional weeks who were hospitalized at a tertiary referral hospital due to confirmed viral LRTI between January 2015 and December 2020. ResultsOf 228 neonates with viral LRTI, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…In spite of the general thought that RSV is the virus most frequently associated with classical respiratory features in premature infants, studies such as ours, in which specific surveillance has been performed, have shown a higher prevalence of non-RSV-related aetiology. These findings are in alignment with other reports wherein nosocomial VRIs in neonates were mostly associated with HCoV infection [ 15 ] or hRV, hMPV, PIV, influenza, hBoV, and HCoV [ 16 ]. These VRIs can cause severe respiratory disease, and in the preterm infant, hRV may be a determinant in the development of complicated LRTIs (apnoea, atelectasis, bacterial superinfection, and sepsis).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In spite of the general thought that RSV is the virus most frequently associated with classical respiratory features in premature infants, studies such as ours, in which specific surveillance has been performed, have shown a higher prevalence of non-RSV-related aetiology. These findings are in alignment with other reports wherein nosocomial VRIs in neonates were mostly associated with HCoV infection [ 15 ] or hRV, hMPV, PIV, influenza, hBoV, and HCoV [ 16 ]. These VRIs can cause severe respiratory disease, and in the preterm infant, hRV may be a determinant in the development of complicated LRTIs (apnoea, atelectasis, bacterial superinfection, and sepsis).…”
Section: Discussionsupporting
confidence: 92%
“…Since the emergence of COVID-19, we have observed a significant reduction in VRI. During the year 2020, the overall number of newborns with lower respiratory tract infection (LRTI) declined significantly, and by the end of the year, some sporadic non-RSV cases were detected, particularly hRV and hMPV infections [ 16 ]. Of note, the observed decrease in VRI rates coincides with the enhancement of infection prevention measures all around the world, including physical distancing, hygiene promotion, and targeted restrictions on gathering and movement [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we could not test for cytokines and chemokines in the CSF. Moreover, RV infection in neonates was shown to be an important risk factor for apnea [ 33 ]. Here, alveolitis and signs of acute hypoxia were observed.…”
Section: Discussionmentioning
confidence: 99%